The map of an unequal city. The spatial distribution of wealth in the city of Buenos Aires in 1839 (Quinto Sol, 2012)
This article studies the spatial distribution of assets such as real state and business capital in the city of Buenos Aires in the mid-nineteenth century. Tax records constitute the principal documentary source; it provides an accurate snapshot of urban wealth and their owners. Mapping and spatial analysis tools are useful to observe the patterns of distribution. We combine the variables of wealth (valuation and access of real property and commercial circuits) with other social and demographic variables, in order to differentiate economic areas in the city. Among the results of this research, we emphasize the existence of a classic pattern of distribution in which the rich center and the poorest suburban periphery feature a contrast. But we also perceive the growing importance of the suburbs as places of accumulation of wealth and opportunities of access to urban land for low and middle social sectors.
Keywords: wealth distribution; spatial inequality; urban real property; Buenos Aires